LncRNA-LINC01089 inhibits lung adenocarcinoma cell proliferation and promotes apoptosis via sponging miR-543. (October 2021) - Xu, Youwen; Lin, Ling; Lv, Dongqing; Yan, Shuangquan; He, Susu; Ge, Hongfei
Highlights: LINC01089 indicated improved overall survival of LUAD patients. LINC01089 was low-expressed in LUAD. Upregulating LINC01089 inhibited LUAD cell proliferation and promoted apoptosis. MiR-543 was targeted by LINC01089, and high-expressed in LUAD tissues in LUAD. The effects of miR-543 and LINC01089 were mutually counteracted in LUAD. Abstract: LINC01089, a newly discovered long non-coding RNA (lncRNA), has been reported to inhibit the progression of various types of cancers. This study aimed to characterize LINC01089 in the pathogenesis of lung adenocarcinoma (LUAD). LINC01089 expression in LUAD tissues or/and cells and its association with the overall survival of LUAD patients was analyzed in The Cancer Genome Atlas (TCGA)-LUAD database, by qRT-PCR or by Kaplan-Meier's curve. Databases of StarBase, LncBase, and DEmiRNA were used to predict and confirm the interaction between LINC01089 and potential LINC01089-targeted microRNAs (miRNAs). The expressions of these miRNAs in LUAD tissues or/and cells were determined by qRT-PCR, and dual-luciferase reporter assay was performed to validate lncRNA-miRNA interaction. The expressions of B-cell lymphoma 2 (Bcl-2), Bcl-2-associated X protein (Bax) and Cleaved caspase-3 in LUAD cells were analyzed by Western blot. LINC01089 improved overall survival of LUAD patients and was low-expressed in LUAD. Upregulating LINC01089 expression reduced LUAD cell viability, inhibited colony formation, enhanced apoptosis, accompanied by downregulated Bcl-2 and miR-543 and upregulated Bax and Cleaved caspase-3. MiR-543 was determined as a target gene of LINC01089, and was high-expressed in LUAD tissues. Upregulating miR-543 expression induced the opposite effects to LINC01089 upregulation on these cellular biological behaviors and the expressions of Bcl-2, Bax and Cleaved caspase-3. Moreover, the effects of miR-543 upregulation and LINC01089 upregulation were mutually counteracted by each other. LINC01089 inhibited lung adenocarcinoma cell proliferation and promoted apoptosis via sponging miR-543.